Syria Economic Monitor - Spring 2022 : Lost Generation of Syrians - World Bank (Washington, DC, 2022)
Now moving into its twelfth year, the conflict in Syria has inflicted a devastating impact on the inhabitants and the economy. Beyond the immediate impact of the conflict, the economy suffers from the compounding effects of the pandemic, adverse weather events, regional fragility, and macroeconomic instability. Economic conditions in Syria are projected to continue to be mired by prolonged armed conflict, turmoil in Lebanon and Turkey, COVID-19, and the war in Ukraine. The conflict in Syria has substantially impacted human lives and dramatically affected the demographic structure of its population. This demographic impact coupled with deteriorating economic conditions have important implications for the labor market, with potential long-lasting repercussions on Syria.